2020
DOI: 10.18203/2320-6012.ijrms20202557
|View full text |Cite
|
Sign up to set email alerts
|

Role of multidetector computed tomography angiography in evaluation of peripheral arterial disease

Abstract: Background: Diagnostic imaging plays an important role in the evaluation of peripheral arterial disease. Many imaging modalities are available ranging from conventional modalities to the cross-sectional modalities like Doppler ultrasound, DSA, CT and MRI. The main principles of imaging are to characterize the all lesions detected including type of plaques, no. of lesions, length of stenosis, diameter of vessel in pre-stenotic and post-stenotic segments, degree of wall calcification, assisting in pretreatment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…In our study, Diabetes mellitus was the major risk factor leading to PAD. Out of 42 patients, 30 patients (86%) were presented with diabetes mellitus that was in accordance with the finding of the study by Kumar R et al 5 while other risk factors noted in our study are hypertension (71%), hyperlipidemia (63%), smoking (57%), cardiac problem (14%) and previous surgery (11%). According to the Kondeti K et al 6 smoking was a major risk factor in the development of PAD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, Diabetes mellitus was the major risk factor leading to PAD. Out of 42 patients, 30 patients (86%) were presented with diabetes mellitus that was in accordance with the finding of the study by Kumar R et al 5 while other risk factors noted in our study are hypertension (71%), hyperlipidemia (63%), smoking (57%), cardiac problem (14%) and previous surgery (11%). According to the Kondeti K et al 6 smoking was a major risk factor in the development of PAD.…”
Section: Discussionsupporting
confidence: 92%
“…So, the results showed that the MDCT was able to detect 9% more diseased segments as compared to doppler USG. Similar finding were noted by Kumar R et al 5 , in which MDCTA showed 11.2% more diseased segments as compared to Doppler.…”
Section: Discussionsupporting
confidence: 89%